Market and regulation: institutional aspects of home water service (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2015)
Whereas scholars of Industrial Economics and Segura (1993), Campbell (1997), Mochón (2000), Nieto (2001), Samuelson and Nordhaus (2006), among others, specific natural resources are governed by market competition imperfect, due to the constraints of the public sector, which translate into legal and administrative constraints. In this regard, the investigation considered theoretical and conceptual aspects market under natural monopoly, state intervention as regulator and some methods for allocating the prices of goods and services subject to monopolies; aiming to describe some institutional aspects of home water service. The methodology proposed finding, analysis and transfer of concepts linked to the theories of monopoly and regulation, using the bibliographic design. The main conclusion is mentioned that economic regulation is to control the production, prices, markets and quality of water resources. Through this measure a dual purpose, such as sustainability and continuity of service companies offering home drinking water and service delivery at low cost in order to benefit the user is fulfilled, preserving the social cost and exercising social regulation.
Keywords: industrial economics; markets; natural monopoly regulation; home water service